Integrated transcriptomic and metabolomic analyses reveal the mechanisms underlying bio-organic fertilizer-mediated growth and nutrient enhancement in Schisandra chinensis (Turcz.) Baill - Xu, Ruiting; Zhang, Wenzhen; Chen, Sihui; Song, Simeng; Dong, Juane; Yang, Zhi; Ma, Yatuan (Frontiers in Plant Science, 2025)
Schisandra chinensis (Turcz.) Baill. is a valuable and widely used traditional Chinese medicine with broad applications. As societal demand grows, enhancing both the yield and quality of this herb has become increasingly important, as these factors directly influence its clinical efficacy. Previous studies have indicated that bio-organic fertilizer can improve the yield and quality of S. chinensis. However, the underlying mechanisms regulating plant growth and nutrient accumulation remain poorly understood. In this study, we investigated the effects of different application rates of bio-organic fertilizer on the growth and nutrient content of S. chinensis. Using transcriptomic and metabolomic approaches, we elucidated the mechanisms by which bio-organic fertilization promotes plant growth and nutrient synthesis. The results demonstrated that the application of bio-organic fertilizer significantly improved the fruits’ morphological traits and yield. Additionally, the contents of beneficial compounds such as lignans, flavonoids, polysaccharides, and polyphenols were elevated. Among all treatments, the application of 100 kg/667 m² bio-organic fertilizer resulted in the highest yield and quality of S. chinensis. Transcriptomic and metabolomic analyses further revealed that bio-organic fertilizer enhances plant growth and nutrient metabolism, consistent with the observed phenotypic improvements. Taken together, this study employs a multi-omics approach to uncover the phenotypic and molecular responses of S. chinensis to bio-organic fertilization. The identified differentially expressed genes and accumulated metabolites provide new insights into the mechanisms by which bio-organic fertilizer improves the quality and yield of S. chinensis.